UPAYA DERADIKALISASI NARAPIDANA TERORISME MELALUI PROGRAM REHABILITASI DI LAPAS - Saputra, Ananda Aldika Ahyu; Subroto, Mitro (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research explores the efforts of deradicalization among terrorist inmates in Indonesian correctional institutions. Based on deradicalization theories, the study highlights various steps taken to reduce the influence of extremism and radicalism among these inmates. Identification, evaluation, and isolation of terrorist inmates are initial stages in the deradicalization process aimed at understanding their motivations and behaviors. The deradicalization program includes education, counseling, skill training, and preparation for post-release social reintegration. Post-release monitoring is also conducted to ensure their non-involvement in terrorist activities. These efforts are grounded in legal principles and statutory regulations governing correctional institutions and counter-terrorism measures. This study provides profound insights into deradicalization practices within correctional institutions, which are essential elements in counterterrorism and the reintegration of terrorist inmates into society. It emphasizes understanding, rehabilitation, and the reduction of radicalism and underscores a research-based approach, along with consultation with experienced experts in developing deradicalization programs. Keywords: Deradicalization; Terrorist Inmates; Correctional Institutions; Rehabilitation